2015
DOI: 10.1016/j.psychres.2015.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Association between social contact frequency and negative symptoms, psychosocial functioning and quality of life in patients with schizophrenia

Abstract: The lack of social contacts may be an important element in the presumed vicious circle aggravating, or at least stabilising negative symptoms in patients with schizophrenia. A European 2-year cohort study collected negative symptom scores, psychosocial functioning scores, objective social contact frequency scores and quality of life scores every 6 months. Bivariate analyses, correlation analyses, multivariate regressions and random effects regressions were conducted to describe relations between social contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
2
17
0
1
Order By: Relevance
“…Negative symptoms of schizophrenia may pose a particular burden to patients, due to their links to lower quality of life and reduced social contact – a recent study, which also used the EuroSC cohort, showed that social isolation in patients with schizophrenia is associated with poor psychosocial functioning and low quality of life (QoL) [21]. Importantly, low level of social activity also aggravates negative symptoms, which further reduce social interactions, forming a vicious circle reinforcing the disease [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative symptoms of schizophrenia may pose a particular burden to patients, due to their links to lower quality of life and reduced social contact – a recent study, which also used the EuroSC cohort, showed that social isolation in patients with schizophrenia is associated with poor psychosocial functioning and low quality of life (QoL) [21]. Importantly, low level of social activity also aggravates negative symptoms, which further reduce social interactions, forming a vicious circle reinforcing the disease [21]. …”
Section: Discussionmentioning
confidence: 99%
“…We used the European Schizophrenia Cohort (EuroSC) – a naturalistic 2-year follow-up of a cohort of 1,208 European schizophrenia patients [14]. Indeed, the EuroSC cohort has been extensively used in past research, which focused on investigating treatment efficacy [15], patients’ quality of life [1618], employment [19], social contact [20,21] and subjective feelings of security and safety [22], as well as assessing caregiver burden [23] and quantifying direct health care costs associated with managing the disease [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…A negative symptom is a reduction or loss of the normal function, consisting of a defective function, such as poor thought, bleak emotion, depression and passive social withdrawal. Negative symptoms can become stable over time and are associated with poor cognitive development, poor premorbid state, drug resistance and poor prognosis in the chronic phases (16). A type of schizophrenia with predominantly negative symptoms is classified as a special group of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A type of schizophrenia with predominantly negative symptoms is classified as a special group of the disease. The analysis of the type of brain connections in cases presenting negative symptoms can reduce the heterogeneity effect of the sample on the study results, and can be useful in elucidating clearly the function of the abnormal brain connections in the pathogenesis of schizophrenia (16). Assuming that FA can reflect the nerve fiber connectivity of the white matter in the brain, the reduction of FA represents damage of regional cerebral white matter integrity and the reduction of nerve fiber connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Penulis melakukan strategi dengan melakukan kontak sosial yang singkat namun sering dalam proses membina hubungan saling percaya. Penelitian menunjukkan adanya hubungan yang signifikan antara frekuensi kontak sosial terhadap gejala negatif, fungsi psikososial dan kalitas hidup klien dengan skizofrenia dimana semakin tinggi kontak sosial klien akan menurunkan gejala negatif skizofrenia dan meningkatkan fungsi sosial secara bersamaan (Siegrist,et al, 2015).…”
Section: Pembahasanunclassified